Natural STAT3 Inhibitors for Cancer Treatment: A Comprehensive Literature Review - Zarezadeh, Seyed M.; Sharafi, Amir Mohammad; Erabi, Gisou; Tabashiri, Arefeh; Teymouri, Navid; Mehrabi, Hoda; Golzan, Seyyed Amirhossein; Faridzadeh, Arezoo; Abdollahifar, Zahra; Sami, Nafiseh; Arabpour, Javad; Rahimi, Zahra; et al. (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Cancer is one of the leading causes of mortality and morbidity worldwide, affecting millions of people physically and financially every year. Over time, many anticancer treatments have been proposed and studied, including synthetic compound consumption, surgical procedures, or grueling chemotherapy. Although these treatments have improved the daily life quality of patients and increased their survival rate and life expectancy, they have also shown significant drawbacks, including staggering costs, multiple side effects, and difficulty in compliance and adherence to treatment. Therefore, natural compounds have been considered a possible key to overcoming these problems in recent years, and thorough research has been done to assess their effectiveness. In these studies, scientists have discovered a meaningful interaction between several natural materials and signal transducer and activator of transcription 3 molecules. STAT3 is a transcriptional protein that is vital for cell growth and survival. Mechanistic studies have established that activated STAT3 can increase cancer cell proliferation and invasion while reducing anticancer immunity. Thus, inhibiting STAT3 signaling by natural compounds has become one of the favorite research topics and an attractive target for developing novel cancer treatments. In the present article, we intend to comprehensively review the latest knowledge about the effects of various organic compounds on inhibiting the STAT3 signaling pathway to cure different cancer diseases.
Keywords: herbal medicine